Living together and Christian ethics - Thatcher, Adrian (New studies in Christian ethics ;, 2002)
Living Together and Christian Ethics is the first positive, in-depth study of cohabitation outside marriage from a mainstream Christian theological perspective. The book retrieves the traditions of betrothal from the Bible and church history, and shows how these can transform Christian attitudes to living together before marriage.